The Construction of Sign that form Kabuyutan Cibulan - Prasetyo, Eko Budi; Nalan, Arthur S; Herdiani, Een (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2023)
Cibulan or known as Cibulan Tourism Object is a place that is believed to be kabuyutan. This belief is not only seen from the myths that develop in the community around Cibulan, but there are signs that exist in Cibulan which are the construction of a kabuyutan. This study uses a paradoxical aesthetic approach belonging to Jakob Sumardjo, namely the triple pattern or tritangtu. The concept of tritangtu is to marry two different things and produce harmony that has the properties of both. Tritangtu is needed because in kabuyutan there must be symbols of Tekad, Ucap, and Lampah which are symbols of Sang Hyang Hurip and tritangtu. In addition to the tritangtu element, kabuyutan must also be built at the confluence of male and female rivers. That is the construction of signs forming kabuyutan where this research will explain the signs and the role of the Cibulan kabuyutan in society.